2011
DOI: 10.1039/c1cc10582e
|View full text |Cite
|
Sign up to set email alerts
|

Pin-point chemical modification of RNA with diverse molecules through the functionality transfer reaction and the copper-catalyzed azide–alkyne cycloaddition reaction

Abstract: The internal modification of RNA has been successfully achieved by the functionality transfer reaction (FTR) and following click chemistry with diverse azide compounds. The benefits of the FTR have been demonstrated by its specificity, rapidity, broad applicability, and procedure simplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…A high selectivity for rC was clearly shown in Figure 3B. The site-specific labeling of rC in RNA has been demonstrated by using an acetylene-functionalized pyridinyl keto unit ( 8 ) for a Cu-catalyzed click reaction with azido derivatives (Biotin-N 3 and FAM-N 3 ) (31)(Supplementary Scheme S2 and Supplementary Figure S3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A high selectivity for rC was clearly shown in Figure 3B. The site-specific labeling of rC in RNA has been demonstrated by using an acetylene-functionalized pyridinyl keto unit ( 8 ) for a Cu-catalyzed click reaction with azido derivatives (Biotin-N 3 and FAM-N 3 ) (31)(Supplementary Scheme S2 and Supplementary Figure S3).…”
Section: Resultsmentioning
confidence: 98%
“…Subsequently, it was found that the transfer reaction was enhanced with selectively for the 2-amino group of the guanine base at alkaline pH or in the presence of NiCl2 at neutral pH (29,30). This method was applied to the site-specific labeling of RNA (31) and O 6 -methyl guanosine-containing DNA (32). The functionality transfer ODN probe (FT-ODN) is advantageous for RNA modification in that the driving force to initiate the transfer reaction is duplex formation with the target RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Functional group transfer has been used to selectively label cytosine and guanine residues in RNA molecules [6,[92][93][94][95] (Fig. 2C).…”
Section: Functionality-transfer Reactionmentioning
confidence: 99%
“…However, over the last few years several research groups have applied the powerful copper-catalyzed azide-alkyne cycloaddition reaction (i.e. CuAAC or click) (2325, 2933) and the strain-promoted azide-alkyne cycloaddition reaction (i.e. SPAAC or copper-free click) to the problem of RNA functionalization (34–35).…”
Section: Introductionmentioning
confidence: 99%
“…Thus the sequence selective binding of the DNA directs the transfer reaction to a specific guanosine in the RNA. They showed this selective reaction could be carried out with a 1,3-diketone transfer group bearing an alkyne to give the guanosine analog 18 (Figure 3) (33). RNA so modified was a substrate for a CuAAC reaction with a fluorescent azide.…”
Section: Introductionmentioning
confidence: 99%